The Welfare Significance of Productive Labour - Myint, Hla (Review of Economic Studies, 1943)
Journal Article The Welfare Significance of Productive Labour Get access Hla Myint Hla Myint Rangoon and Manchester Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 11, Issue 1, Winter 1943, Pages 20–30, https://doi.org/10.2307/2967516 Published: 01 December 1943